Laryngeal neurofibroma associated with neurofibromatosis type 2 - Cihangiroglu, M; Yilmaz, S; Topsakal, C; Gok, U; Altinsoy, B; Cobanoglu, B (Amer Soc Neuroradiology, 2002)
We present a case of laryngeal neurofibroma associated with neurofibromatosis type 2. Although laryngeal neurofibromas have previously been reported in cases of neurofibromatosis type 1, their presence has never been described in a patient with neurofibromatosis type 2.
Keywords: Mr; Tumors